The Potential Role of Matrix Metalloproteinases 8 and 9 and Myeloperoxidase in Predicting Outcomes of Bacterial Meningitis of Childhood - Savonius, Okko; Roine, Irmeli; Alassiri, Saeed; Tervahartiala, Taina; Helve, Otto; Fernández, Josefina; Peltola, Heikki; Sorsa, Timo; Pelkonen, Tuula (Mediators of Inflammation, 2019)
Background. Matrix metalloproteinases (MMPs) and myeloperoxidase (MPO) contribute to the inflammatory cascade in the cerebrospinal fluid (CSF) during bacterial meningitis. We determined levels of MPO, MMP-8, MMP-9, and tissue inhibitor of metalloproteinase- (TIMP-) 1 in the CSF of children with bacterial meningitis and investigated how these inflammatory mediators relate to each other and to the disease outcomes. Methods. Clinical data and the diagnostic CSF samples from 245 children (median age eight months) with bacterial meningitis were obtained from a clinical trial in Latin America in 1996–2003. MMP-9 levels in the CSF were assessed by zymography, while MMP-8, MPO, and TIMP-1 concentrations were determined with immunofluorometric and enzyme-linked immunosorbent assays. Results. MPO correlated positively with MMP-8 (rho 0.496, P<0.001) and MMP-9 (rho 0.153, P=0.02) but negatively with TIMP-1 (rho -0.361, P<0.001). MMP-8 emerged as the best predictor of disease outcomes: a CSF MMP-8 concentration above the median increased the odds of death 4.9-fold (95% confidence interval 1.8–12.9). Conclusions. CSF MMP-8 presented as an attractive prognostic marker in children with bacterial meningitis.